PENGARUH KELEKATAN ORANG TUA TERHADAP DOMAIN SOSIAL PADA MAHASISWA TINGKAT AKHIR - Salsabila, Salsabila; Fahmi, Abu Bakar (Psikologi UHAMKA, 2021)
While completing a thesis, students need social support from the people around them. The source of social support comes from a group of social situations called the social domain. Previous research has found that parental attachment affects the social domain of early-year college students. This study aims to determine the role of parental attachment to the social domain in final year students. Respondents in this study amounted to 234 active final year students who are working on a thesis. The instruments used to measure parental attachment and social domains were The Continued Attachment Scale with 12 items and The Social Provisions Scale with 24 items, respectively. Simple linear regression test was conducted to determine whether there is an effect of parental attachment to the social domain in final year students. A significant regression equation was found, F(1, 232) = 6.245; p = 0.013; R2 = 0.026. These results indicate that there is a significant influence of parental attachment to the social domain in final year students.